Measuring the technical efficiency of decision-making units using the Data Envelopment Analysis (DEA) method. Field research in the General Land Transport Company. - Salah al - Din Awad al - Kubaisi; Laith Khalil Ibrahim (Iraqi Journal for Administrative Sciences, 2025)
this research aims it measure the technical efficiency of the branches of the General Company for Land Transport, That scattered geographically at country level, by Data Envelopment analysis (DEA) technique, as this technique relies on measuring the efficiency of a set of asymmetric Decision making units, which is one of the nonparametric mathematical methods for and application related to Linear Programming, and this is what helps the General Company for Land Transport to diagnose its branches performance by benchmarking with each other and determine the performance gap. The research found that there is variation in the level of efficiency in the company's branches.